2017
DOI: 10.1002/polb.24285
|View full text |Cite
|
Sign up to set email alerts
|

Thickness‐dependent swelling of molecular layer‐by‐layer polyamide nanomembranes

Abstract: The thickness‐dependent water vapor swelling of molecular layer‐by‐layer polyamide films is studied via specular X‐ray reflectivity. The maximum swelling ratio of these ultrathin films scale inversely with thickness but more importantly show a dual‐mode sorption behavior characterized by Langmuir‐like sorption at low relative humidity and network swelling at high relative humidity. The thickness‐dependent network parameters are extracted using a proposed model that builds on Painter‐Shenoy network swelling mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 21 publications
3
23
0
Order By: Relevance
“…Formally, the organic-soluble component (acid chloride) is insoluble into the polymer, whereas the water-soluble component (diamine) diffuses through the film to react with the acid chloride at the film/organic phase interface, where the film grows. [25,30,31] Toward this goal, considerable effort has been dedicated to the structural characterization of the skin layer of commercially available RO membranes, [26,[28][29][30][31][32][33][34][35][36][37] generally carried out under vacuum (away from operating conditions), molecular modeling, [38][39][40][41][42][43] or by developing more controlled synthetic pathways. [27] Despite being widely used on an industrial scale, membranes obtained via IP are generally inhomogeneous in terms of spatial variation, chemistry, and porosity at the micrometer to nanoscales.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Formally, the organic-soluble component (acid chloride) is insoluble into the polymer, whereas the water-soluble component (diamine) diffuses through the film to react with the acid chloride at the film/organic phase interface, where the film grows. [25,30,31] Toward this goal, considerable effort has been dedicated to the structural characterization of the skin layer of commercially available RO membranes, [26,[28][29][30][31][32][33][34][35][36][37] generally carried out under vacuum (away from operating conditions), molecular modeling, [38][39][40][41][42][43] or by developing more controlled synthetic pathways. [27] Despite being widely used on an industrial scale, membranes obtained via IP are generally inhomogeneous in terms of spatial variation, chemistry, and porosity at the micrometer to nanoscales.…”
Section: Introductionmentioning
confidence: 99%
“…[21,22] The resulting cross-linked polyamide (PA) film has an overall "apparent" film thickness of, typically, a few hundred nm, and is rough and crumpled, with individual PA film thickness of the order of 10 nm, as revealed by recent high-resolution imaging reports, [23][24][25][26] supported by a porous polysulfone layer with a heterogeneous nanoscale interface layer. [37,[44][45][46][47][48] These include spinassisted molecular layer-by-layer (mLbL) techniques, [37,44,45] and ultrathin films synthesized on Cd(OH) 2 nanowires [46] and carbon nanotube supports, [47] or a cellulose nanocrystal interlayer, [48] seeking to fabricate highly controlled PA thin films, and systematically correlate film thickness, roughness, and membrane performance. [28,29] Although the interplay between the top layer and porous support is important for the membrane properties and, for instance, the support layer undergoes compaction during operation [10] thus contributing to a reduction in flux, the actual separation process is governed by the PA skin layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Characterizing the chemistry of a bulk polyamide sample is straightforward, but characterizing these chemical moieties for ultrathin polyamide films is nontrivial as they are ≈100 nm thick. Additionally, the degree of compositional homogeneity in these films is unclear, and it would be significantly beneficial to quantify the potential depth-dependent heterogeneity [6,7]. …”
mentioning
confidence: 99%
“…We attribute the slight discrepancies to either the thickness-dependent crosslink density or the presence of network defects. Chan et al have recently reported the thickness-dependent crosslink density of P m PDTA thin films to show that the crosslink density increases with increasing film thickness up to ≈ 72 nm [7]. Network defects such as dangling bonds will affect the swelling behavior, and thus the pore size, of a polymer network.…”
mentioning
confidence: 99%